New dictionary of the history of ideas - Horowitz, Maryanne Cline (Charles Scribner’s Sons, 2005)
From abolitionism to Zionism, this encyclopedia clarifies the intellectual history of more than 750 complex ideas of concern to people today. Like its classic predecessor, the Dictionary of the History of Ideas (1973), this new set covers core Western ideas, while expanding its coverage to include the ’global perspectives and gender-inclusive’ concepts that have evolved in the past 30 years. Reader’s guides, cross-references, sidebars, and an index aid the reader in understanding the way ideas combine with other ideas."--"Reference that rocks," American Libraries, May 2005